Immunization status in patients with multiple sclerosis: A cross‐sectional, monocenter study in Austria. (26th February 2023) - Berek, Klaus; Deisl, Philipp; Bichler, Maximilian; Auer, Michael; Barket, Robert; Bauer, Angelika; Zinganell, Anne; Di Pauli, Franziska; Deisenhammer, Florian; Hegen, Harald
Abstract: Background and purpose: Patients with multiple sclerosis (MS) under certain disease‐modifying therapies (DMT) show a higher risk of infection and a lower immune response to vaccination. Hence, assessing immunization status prior to DMT start and, where necessary, performing vaccinations is  recommended. We aimed to determine the immunization status in MS patients and to identify factors associated with low vaccination rates. Methods: Patients with MS who were seen at the MS clinic of the Medical University of Innsbruck throughout a period of 14 months in 2020 and 2021 were eligible for inclusion into this prospective, single‐center study. Immunization status against 17 different pathogens was obtained from vaccination certificate and by patient questionnaire. Antibody detection against seven antigens was performed in peripheral blood. Results: Of 424 patients with MS at a mean age of 43 ± 12 years, the vast majority had vaccinations against tetanus (94%), diphtheria (92%), and poliomyelitis (90%), whereas a lower proportion had vaccinations against tick‐borne encephalitis (70%), pertussis (69%), hepatitis B (65%), rubella (55%), hepatitis A (50%), measles (49%), mumps (47%), and only a minority against influenza (10%), pneumococcal (6%) and meningococcal disease (4%), human papillomavirus (4%), yellow fever (2%), and varicella zoster virus (1%). A total of 87% received vaccination against SARS‐CoV‐2. Overall, higher vaccination rates were associated with younger age, relapsing disease course, and education level. Misinformation on infectious diseases and vaccines was associated with lower vaccination rates. Conclusions: The majority of MS patients did not fulfil vaccination recommendations. Efforts to increase vaccination rates, preferentially before DMT start, should be promoted.